Effect of Si content on microstructure and thermo-physical properties of the joint of Sip/6063Al composite by laser melting deposition. (1st December 2017) - Lei, Zhenglong; Tian, Ze; Li, Peng; Chen, Yanbin; Zhang, Hengquan; Gu, Jingyan; Su, Xuan
Highlights: Butt welding of Sip /6063Al composite sheets was conducted using laser melting deposition. The joints were composed of irregular-shape Si, circled α-Al and (Al, Si) eutectic matrix phases. Thermal physical properties of the joints were studied. Abstract: Laser melting deposition (LMD), an additive manufacturing-based technology, was utilized to join Sip /6063Al composite creatively with different Si weight contents (Al-Si 5%, 12%, 20% and 30%). Influence of the Si content on the constitutional phases, microstructural characteristics, and thermo-physical properties of the layer by layer built-up weld beads was investigated. Experimental results showed that the increasing of deposited Si content could lead to a marked increment of both size and volume of precipitated Si phase, and the circled α-Al phase decreased as a whole. The Si/Al interface began to decrease for the sample Al-Si30 wt.% due to the connection of Si phases. The α-Al phase within the (Al, Si) eutectic were observed to exhibit two sub-micron solidification morphologies, columnar grains and equiaxed grains, respectively. In general, by increasing the content of the deposited Si, the thermal conductivity decreased owing to the decreasing of α-Al phase with high conductivity, and the coefficient of thermal expansion (CTE) had the same varying trend which was attributed to the increasing volume fraction of stiff precipitated Si phase and Si-Si contiguity.